Imaging: Conjugated Polymer Amplified Far‐Red/Near‐Infrared Fluorescence from Nanoparticles with Aggregation‐Induced Emission Characteristics for Targeted In Vivo Imaging (Adv. Healthcare Mater. 3/2013). Issue 3 (6th March 2013) - Ding, Dan; Li, Kai; Qin, Wei; Zhan, Ruoyu; Hu, Yong; Liu, Jianzhao; Tang, Ben Zhong; Liu, Bin
<x xml:space="preserve">Abstract</x> Bin Liu and co‐workers report on page 500 a fluorescence‐amplified far‐red/near‐infrared (FR/NIR) probe by co‐encapsulation of a conjugated polymer donor and a fluorogen acceptor with aggregation‐induced emission (AIE) characteristics into biocompatible bovine serum albumin (BSA) matrix. These probes allow for targeted in vitro and in vivo cancer imaging with high contrast and in a selective manner. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>